Adaptasi Mahasiswa Asing Di Universitas Muhammadiyah Surakarta - Widyaningrum, Mentari Ika, Ratri Kusumaningtyas, M.Si (2017)
There aducational needs make foreign student immigrated to UMS and have to adapt to new and different culture. Based on this background the authors found the problem, adaptation of foreign students in college environtment. This study used theoryStress-Adaptation-Growth Dynamic by young yun kim. This research used qualitative descriptive approach with purposive sampling method, and to check the validity of the data used trianggulasi data. The results showed that each foreign student have their own way in the process of adaptation and they managed to adapt, and smile can be easiest way to start adaptation. The adaptation is like motivate youre self and remind that main purpose is to study, make youre self comfortable with environtment, and mutual respect for religion and culture for priceless experience, and they will to accept.